Depression as a Trigger of Personality Alteration in The Fault in Our Stars by John Green (Faculty of Letters Universitas Balikpapan, 2022)
The research focuses on the forms of depression that happen and the effect of personality alteration in The Fault in Our Stars by John Green. The aim of this research is to find the forms of depression and effects to personality alteration. The theory used in this research is Psychoanalysis theory by Carl Jung and Aaron Beck's theory of depression to find the forms of depression. The methodology employed is qualitative research in which the researcher presents the issue descriptively. As for the data, they were collected from the text of the novel. The novel is the primary data. Based on the results of this study, the researcher found that depression has more effects on extrovert personality alteration and emotional depression is the greatest effect.